FERTILITY AND INFERTILITY IN COUPLES OF REPRODUCTIVE AGE: A SCOPING REVIEW - Novitasari Novitasari; Rismawati Rismawati; Qonita Qonita (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Fertility and infertility are major issues in global reproductive health influenced by various biological, hormonal, environmental, and medical factors. Infertility affects approximately 8–12% of couples worldwide, and several studies indicate that the prevalence continues to increase due to lifestyle changes and exposure to risk factors. Ovarian factors, tubal disorders, spermatogenesis, reproductive age, and metabolic conditions such as Polycystic Ovary Syndrome (PCOS) play important roles in determining fertility outcomes.  To comprehensively analyze scientific evidence regarding the determinants of fertility and infertility among couples of reproductive age, as well as to describe clinical implications and evidence-based recommendations. This study employed a scoping review design conducted through searches of scientific articles in PubMed Central, BioMed Central, and Google Scholar Open Access. Eligible articles were full-text publications in English published between 2016 and 2025. Most studies indicated that female infertility is associated with ovulatory disorders, tubal damage, diminished ovarian reserve, and endometriosis, whereas male infertility is commonly influenced by sperm quality, varicocele, reproductive tract infections, and genetic factors. In addition, age, obesity, smoking, oxidative stress, and exposure to toxic environmental factors were also associated with reduced chances of pregnancy. Assisted Reproductive Technologies (ART), such as In Vitro Fertilization (IVF) and Intracytoplasmic Sperm Injection (ICSI), have been shown to improve fertility outcomes; however, their success rates are highly dependent on the age and baseline conditions of the couples. Infertility is caused by multifactorial interactions involving biological, hormonal, and environmental aspects. Early detection of reproductive disorders, education regarding healthy lifestyles, and access to fertility services are essential to improve the chances of achieving pregnancy.